Image-Based Computational Modeling of the Human Circulatory and Pulmonary Systems Methods and Applications - Chandran, Krishnan B.; Udaykumar, H. S.; Reinhardt, Joseph M. (Springer eBooks., 2011)
Image-Based Computational Modeling of the Human Circulatory and Pulmonary Systems provides an overview of the current modeling methods and applications enhancing interventional treatments and computer-aided surgery. A detailed description of the techniques behind image acquisition, processing and three-dimensional reconstruction are included. Techniques for the computational simulation of solid and fluid mechanics and structure interaction are also discussed, in addition to various cardiovascular and pulmonary applications. Engineers and researchers involved with image processing and computational modeling of human organ systems will find this a valuable reference.